Thermal analysis of quaternary molten nitrate salts mixture for energy recovery system - Tukimon, Mohd Faizal; Wan Muhammad, Wan Nur Azrina; Mohamad, Md Nor Anuar; Rosly, Nurhayati; Mat Isa, Norasikin (Trans Tech Publications, 2019)
Quaternary molten salt nitrate have been used very practically as medium for energy storage or heat transfer fluid in terms of energy recovery system. Quaternary molten salt nitrate is a mixture that can transfer heat to generate energy such as electricity. Mixed alkaline molten nitrate salt can act as a heat transfer fluid due to their advantageous in terms of heat recovery system due to high specific heat capacity, low vapour pressure, low cost and wide range of temperature in its application. This studies shows about determining the new composition of quaternary molten nitrate salts from different primary salts that can possibly give a high specific heat capacity with low melting point. The mixture of quaternary molten nitrate salts was then heated inside the box furnace at 150oC for four hours and rose up the temperature to 400oC for eight hours. Through heating process, the quaternary molten nitrate alkaline was completely homogenized. The temperature was then dropped to room temperature before removing the mixture from the furnace. The specific heat capacities of each sample were determined by using Differential Scanning Calorimeter, DSC. From the result of DSC testing, Sample 6 gives the highest point of specific heat capacity and low melting point which is 0.4648 J/goC and 97.71oC respectively. In the nut shell, Sample 6 was chosen as a good mixture with good thermal properties that has a low melting point which is below 100oC but high specific heat capacity that may be a helpful in the application energy recovery system.